FOOD AS A TOURISM COMPETITIVENESS FACTOR OF JABLANICA DISTRICT IN SERBIA - Stamenković, Predrag; Djeri, Lukrecija (Economics of Agriculture, 2016)
Jablanica district represents mainly rural and economically underdeveloped part of Serbia. However, it is characterized by a favorable geographical position, great natural and cultural resources, which are not yet adequately valorized and presented on the tourism market. This paper, with appropriate statistical procedures, processes both, importance and performance factors of tourist destination, and identifes food as a factor of primary importance for improvement of tourism competitiveness in the Jablanica district. The results of this study could be of great importance for tourism managers in the destination, as well as for local government authorities, to understand better the importance of the identifed competitiveness factors, and provide them a good starting point for tourism development.